Życie literackie Łodzi w czasie I wojny światowej - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Łódź that has never had significant literary tradition, reached a few interesting debuts of young artists during the dramatic years of the war. Tuwim siblings should be named among them, along with Aleksander Kraśniański and Mieczysław Braun. Multi-ethnicity of Lodz resulted in a diverse view on the ongoing conflict, which found its echo in the work of local writers. In their works we find descriptions of both the drama of everyday life as well as questions about the meaning of the war and the future of the reborn state. Since there was problem with publishing books, the local newspaper publishes gave enormous contribution to the development of local literature by publishing the work of young artists on its pages.